DEEP LAYERS OF BEING ARTISTIC TEXT - Ципердюк, О. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Book review on: Khudozhniy text – slovo – obraz : lingvostylistychnyy analiz : monografiya / [М. І. Holyanych, І. О. Babiy, N. Ya. Ivanyshyn ta іn.]; za red. М. І. Holyanych. – Іvano-Frankivsk : Vydavnytstvo Prykarpatskoho natsionalnoho universytetu іmeni Vasylya Stefanyka, 2010. – 408 s.